Equilibrium Learning in Auction Markets - Heidekrüger, Stefan (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
My dissertation investigates the computation of Bayes-Nash equilibria in auctions via multiagent learning. A particular focus lies on the game-theoretic analysis of learned gradient dynamics in such markets. This requires overcoming several technical challenges like non-differentiable utility functions and infinite-dimensional strategy spaces. Positive results may open the door for wide-ranging applications in Market Design and the economic sciences.